Longitudinal course of epilepsy in Rett syndrome and related disorders - Daniel Tarquinio; Wei Hou; Anne T. Berg; Walter E. Kaufmann; Jane B. Lane; Steven A. Skinner; Kathleen J. Motil; Jeffrey L. Neul; Alan K. Percy; Daniel G. Glaze (2016)
Epilepsy is common in Rett syndrome, an X-linked dominant disorder caused by mutations in the MECP2 gene, and in Rett-related disorders, such as MECP2 duplication. However, neither the longitudinal course of epilepsy nor the patterns of seizure onset and remission have been described in Rett syndrome and related conditions. The present study summarizes the findings of the Rett syndrome Natural History study. Participants with clinical Rett syndrome and those with MECP2 mutations without the clinical syndrome were recruited through the Rett Natural History study from 2006 to 2015. Clinical details were collected, and cumulative lifetime prevalence of epilepsy was determined using the Kaplan-Meier estimator. Risk factors for epilepsy were assessed using Cox proportional hazards models. Of 1205 participants enrolled in the study, 922 had classic Rett syndrome, and 778 of these were followed longitudinally for 3939 person-years. The diagnosis of atypical Rett syndrome with a severe clinical phenotype was associated with higher prevalence of epilepsy than those with classic Rett syndrome. While point prevalence of active seizures ranged from 30% to 44%, the estimated cumulative lifetime prevalence of epilepsy using Kaplan-Meier approached 90%. Specific MECP2 mutations were not significantly associated with either seizure prevalence or seizure severity. In contrast, many clinical features were associated with seizure prevalence; frequency of hospitalizations, inability to walk, bradykinesia, scoliosis, gastrostomy feeding, age of seizure onset, and late age of diagnosis were independently associated with higher odds of an individual having epilepsy. Aggressive behaviour was associated with lower odds. Three distinct patterns of seizure prevalence emerged in classic Rett syndrome, including those who did not have seizures throughout the study, those who had frequent relapse and remission, and those who had relentless seizures. Although 248 of those with classic Rett syndrome and a history of seizures were in terminal remission at last contact, only 74 (12% of those with a history of epilepsy) were seizure free and off anti-seizure medication. When studied longitudinally, point prevalence of active seizures is relatively low in Rett syndrome, although lifetime risk of epilepsy is higher than previously reported. While daily seizures are uncommon in Rett syndrome, prolonged remission is less common than in other causes of childhood onset epilepsy. Complete remission off anti-seizure medications is possible, but future efforts should be directed at determining what factors predict when withdrawal of medications in those who are seizure free is propitious.